The Influence of Dynamic Pricing in Enhancing Room Occupancy and Room Revenue in Bintan Island Resort - Hidayati, Sadila; Hadi Nata, Jiwangga; Reindrawati, Dian Yulie; Nurul Huda, Mohammad (TIJAB (The International Journal of Applied Business), 2025)
Background: Dynamic demand-based pricing has increasingly been adopted by capacity-constrained businesses such as hotels. This strategy is deemed highly profitable for both service providers and guests. Resorts on Bintan Island have implemented dynamic pricing by analyzing specific dates and times when occupancy is expected to peak. Objective: This research aims to analyze the impact of dynamic pricing on hotel reservations and revenue, focusing on its effect on increasing room occupancy and revenue. Method: The study utilizes descriptive quantitative research methods, relying on primary data from the Daily on the Book (OTB) Report, Dynamic Cover Monthly Report, and Three Month Forecast Report, all sourced from the hotel Property Management System (PMS) called Opera. Results: The findings indicate that dynamic pricing significantly increases hotel room occupancy and revenue. Conclusion: Hotel management must choice between prioritizing occupancy or room revenue. The room nights and occupancy budget might not be reached if management prioritizes increasing room revenue and vice versa. Keywords: dynamic pricing, occupancy, revenue, Average Daily Rates (ADR), reservation